Kamishibai, booktalking, storytelling…, czyli formy pracy z młodym czytelnikiem - Lisowska-Kożuch, Urszula (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2015)
The article is an introduction to the issue of the forms of working with a library attendee. Basing on the subject literature, the currently used selections of forms were presented, including the examples of them. The Author also presents the results of studies conducted on this field in selected libraries. The description of the forms also includes directions referring to them, which can be found in binding legal acts and documents, especially the ones issued by IFLA and UNESCO.